Periodontal Systemic Connections-Novel Associations-A Review of the Evidence with Implications for Medical Practitioners - Kalakonda, Butchibabu; Koppolu, Pradeep; Baroudi, Kusai; Mishra, Ashank (International Journal of Health Sciences, 2016)
Â  Â  Â Periodontal diseases, considered as inflammatory diseases have proved to have a spectrum of systemic implications. Earliest research has associated periodontal disease with common systemic aliments such as hypertension, diabetes, osteoporosis, rheumatoid arthritis to name a few. The evolution of advanced diagnostic aids let researchers make vast inroads in linking periodontal diseases to systemic diseases like Alzheimerâ€™s disease (AD) and even Schizophrenia. Our aim was to review and critically evaluate comprehensive literature and provide knowledge to medical practitioners on these associations so as to pave way for closer interactions between medical and dental practitioners in implementing better health care. Â Â Â Â  Electronic databases such as PubMed, Google Scholar and Cochrane databases were used as source of the data for relevant studies published from 2005 up to 2015 with the following keywords, â€œâ€˜Periodontal diseaseâ€, â€œsystemic conditionsâ€, â€œperiodontal disease and Alzheimerâ€™sâ€, â€œPeriodontal disease and Schizophreniaâ€, â€œPeriodontal disease and Psoriasisâ€ and â€œPeriodontal disease and erectile dysfunctionâ€. Â Â Â Â  The evidence presented ascertains that a reasonable and modest association does exist between Periodontal disease and Alzheimerâ€™s, Schizophrenia, Erectile dysfunction, as well as Psoriasis and thus establishes periodontal disease as a potential risk factor. Keywords: Alzheimerâ€™s disease, Erectile dysfunction, Periodontal disease, Psoriasis, Systemic diseases, Schizophrenia. Â 